The Role of NGOs in Ameliorating Sweatshop‐like Conditions in the Global Supply Chain: The Case of Fair Labor Association (FLA), and Social Accountability International (SAI). (March 2016) - Sethi, S. Prakash; Rovenpor, Janet L.
Abstract: Over the last 20+ years, globalization has made international trade and investment more efficient and productive. In the absence of coordinated global regulatory regimes, it has also made multinational corporations (MNCs) impervious to social concerns in the countries where they operate. There is considerable debate in the academic, political, and business arena as to the causes of the apparently inequitable distribution of benefits between labor and capital. Notwithstanding, the relative merits of this debate, and facing tremendous societal pressure, companies have adopted voluntary codes of conduct to ensure that workers making products for them in poor and developing countries are protected from hazardous working conditions and receive wages that meet local laws and market conditions. These codes, however, suffer from a lack of credibility and proof of substantive compliance. A new type of nongovernmental organization (NGO) has emerged that monitors a company's compliance with prespecified standards and provides assurance to the external stakeholders that the company has fulfilled its voluntary obligations. From an historical perspective, this has been an innovative phenomenon where the monitoring organization purports to act as an honest broker to ensure all concerned that the company/industry has fulfilled its obligations. In this article, we undertake a thorough examination of two such organizations, that is, Fair Labor Association, and Social Accountability International, that have played a pioneering role in bridging the gap between societal expectations and corporate performance. We examine their governance structures, operating procedures, monitoring standards, and public disclosure of findings, and above all, their success in improving the level of corporate compliance with their self‐created codes or standards. Unfortunately, our findings and conclusions are disappointing. In our view, the two groups have mostly failed to meet their avowed goals. Rather than using their NGO status to help companies improve their code compliance, they have suffered from managerial capture and have been reduced to corporate apologists.